Sneaking into the viral safe-houses: Implications of host components in regulating integrity and dynamics of rotaviral replication factories - Chandra, Pritam; Banerjee, Shreya; Saha, Priyanka; Chawla-Sarkar, Mamta; Patra, Upayan (Frontiers in Cellular and Infection Microbiology, 2022)
The biology of the viral life cycle essentially includes two structural and functional entities—the viral genome and protein machinery constituting the viral arsenal and an array of host cellular components which the virus closely associates with—to ensure successful perpetuation. The obligatory requirements of the virus to selectively evade specific host cellular factors while exploiting certain others have been immensely important to provide the platform for designing host-directed antiviral therapeutics. Although the spectrum of host-virus interaction is multifaceted, host factors that particularly influence viral replication have immense therapeutic importance. During lytic proliferation, viruses usually form replication factories which are specialized subcellular structures made up of viral proteins and replicating nucleic acids. These viral niches remain distinct from the rest of the cellular milieu, but they effectively allow spatial proximity to selective host determinants. Here, we will focus on the interaction between the replication compartments of a double stranded RNA virus rotavirus (RV) and the host cellular determinants of infection. RV, a diarrheagenic virus infecting young animals and children, forms replication bodies termed viroplasms within the host cell cytoplasm. Importantly, viroplasms also serve as the site for transcription and early morphogenesis of RVs and are very dynamic in nature. Despite advances in the understanding of RV components that constitute the viroplasmic architecture, knowledge of the contribution of host determinants to viroplasm dynamicity has remained limited. Emerging evidence suggests that selective host determinants are sequestered inside or translocated adjacent to the RV viroplasms. Functional implications of such host cellular reprogramming are also ramifying—disarming the antiviral host determinants and usurping the pro-viral components to facilitate specific stages of the viral life cycle. Here, we will provide a critical update on the wide variety of host cellular pathways that have been reported to regulate the spatial and temporal dynamicity of RV viroplasms. We will also discuss the methods used so far to study the host-viroplasm interactions and emphasize on the potential host factors which can be targeted for therapeutic intervention in the future.